2019
DOI: 10.3390/medsci7080086
|View full text |Cite
|
Sign up to set email alerts
|

Origins and Impact of Psychological Traits in Polycystic Ovary Syndrome

Abstract: Women with polycystic ovary syndrome (PCOS) exhibit compromised psychiatric health. Independent of obesity, women with PCOS are more susceptible to have anxiety and depression diagnoses and other neuropsychiatric disorders. During pregnancy women with PCOS display high circulating androgen levels that may cause prenatal androgen exposure affecting the growing fetus and increasing the risk of mood disorders in offspring. Increasing evidence supports a non-genetic, maternal contribution to the development of PCO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 70 publications
1
16
0
Order By: Relevance
“…Male offspring with ancestral DHEA exposure showed lower sperm quality. There is evidence that a significant correlation exists between the prenatal and early postnatal environment of PCOS women and their pregnancy outcomes (24,26). Continuous injection of androgens or their metabolites is commonly used to replicate PCOS-like phenotypes in rodents.…”
Section: Discussionmentioning
confidence: 99%
“…Male offspring with ancestral DHEA exposure showed lower sperm quality. There is evidence that a significant correlation exists between the prenatal and early postnatal environment of PCOS women and their pregnancy outcomes (24,26). Continuous injection of androgens or their metabolites is commonly used to replicate PCOS-like phenotypes in rodents.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual dysfunction [163] and depression [164] are increasingly coincident sequelae in women with PCOS [21]. Four macaque models of PCOS are potentially of relevance to their developmental origins.…”
Section: Behavioral Pcos-related Traits In Macaque Modelsmentioning
confidence: 99%
“…The risk of anxiety and depression was significantly increased in patients with PCOS. Relevant research showed that more than 60% of PCOS patients were diagnosed with at least one kind of mental disorder [ 122 ]. The severity of depression, anxiety, obsessive-compulsive disorder, and somatization disorder measured by different scales in PCOS patients was higher than that in women without PCOS [ 123 ].…”
Section: Meditation Stress Reductionmentioning
confidence: 99%